Technique-dependent relationship between local ski bending curvature, roll angle and radial force in alpine skiing - Thorwartl, C.; Tschepp, A.; Lasshofer, M.; Holzer, H.; Zirkl, M.; Hammer, M.; Stadlober, B.; Stöggl, T. (Sensors, 2023)
Skiing technique, and performance are impacted by the interplay between ski and snow. The resulting deformation characteristics of the ski, both temporally and segmentally, are indicative of the unique multi-faceted nature of this process. Recently, a PyzoFlex® ski prototype was presented for measuring the local ski curvature (w''), demonstrating high reliability and validity. The value of w'' increases as a result of enlargement of the roll angle (RA) and the radial force (RF) and consequently minimizes the radius of the turn, preventing skidding. This study aims to analyze segmental w'' differences along the ski, as well as to investigate the relationship among segmental w'', RA, and RF for both the inner and outer skis and for different skiing techniques (carving and parallel ski steering). A skier performed 24 carving and 24 parallel ski steering turns, during which a sensor insole was placed in the boot to determine RA and RF, and six PyzoFlex® sensors were used to measure the w'' progression along the left ski (w''1-6). All data were time normalized over a left-right turn combination. Correlation analysis using Pearson`s correlation coefficient (r) was conducted on the mean values of RA, RF, and segmental w''1-6 for different turn phases [initiation, center of mass direction change I (COM DC I), center of mass direction change II (COM DC II), completion]. The results of the study indicate that, regardless of the skiing technique, the correlation between the two rear sensors (L2 vs. L3) and the three front sensors (L4 vs. L5, L4 vs. L6, L5 vs. L6) was mostly high (r > 0.50) to very high (r > 0.70). During carving turns, the correlation between w'' of the rear (w''1-3) and that of front sensors (w''4-6) of the outer ski was low (ranging between -0.21 and 0.22) with the exception of high correlations during COM DC II (r = 0.51-0.54). In contrast, for parallel ski steering, the r between the w'' of the front and rear sensors was mostly high to very high, especially for COM DC I and II (r = 0.48-0.85). Further, a high to very high correlation (r ranging between 0.55 and 0.83) among RF, RA, and w'' of the two sensors located behind the binding (w''2,w''3) in COM DC I and II for the outer ski during carving was found. However, the values of r were low to moderate (r = 0.04-0.47) during parallel ski steering. It can be concluded that homogeneous ski deflection along the ski is an oversimplified picture, as the w'' pattern differs not only temporally but also segmentally, depending on the employed technique and turn phase. In carving, the rear segment of the outer ski is considered to have a pivotal role for creating a clean and precise turn on the edge.